Analisis Nilai-Nilai Komunikasi Islam dalam Tradisi Tepung Tawar Masyarakat Melayu - Tania Dwi Putri; Hendra Hendra; Lidiya Lidiya; Ayu Adesma (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
The Tepung Tawar Tradition is one of the cultural heritages of the Malay community that continues to be preserved today, particularly in various traditional ceremonies such as weddings, circumcisions, thanksgiving events, and the welcoming of honored guests. This tradition functions not only as a customary ritual but also embodies social, cultural, and religious values that have been passed down from generation to generation. This study aims to analyze the Islamic communication values contained in the Tepung Tawar Tradition of the Malay community in Natuna. The research employed a qualitative approach using field research methods. Data were collected through observation, interviews, and documentation. The research informants were community leaders who have a deep understanding of the implementation of the Tepung Tawar Tradition, one of whom was Mr. Suhaili. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the Tepung Tawar Tradition contains values of bil lisan communication through prayers, shalawat, and advice; bil hal communication through customary symbols and actions; the value of ukhuwah Islamiyah that strengthens social relationships within the community; and the value of cultural da'wah that integrates Malay culture with Islamic teachings. Furthermore, this tradition serves as a medium for Islamic values education and as a means of preserving the cultural identity of the Malay community in Natuna. This study offers novelty by examining the Tepung Tawar Tradition not merely as a Malay cultural practice, but also as a medium of Islamic communication that embodies the values of bil lisan communication, bil hal communication, Islamic brotherhood (ukhuwah Islamiyah), and cultural da'wah within the context of the Malay community of Natuna.